The patron's payoff conspicuous commissions in Italian Renaissance art - Nelson, Jonathan K. 1961-; Zeckhauser, Richard 1940- (Princeton Univ. Press, 2008)
An analysis of Italian Renaissance art from the perspective of the patrons who made 'conspicuous commissions', this text builds on three concepts from the economics of information - signaling, signposting, and stretching - to develop a systematic methodology for assessing the meaning of patronage.
Includes index.
Keywords: Geschichte 1420-1600; Art patronage -- Italy; Artists and patrons -- Italy; Art, Renaissance -- Italy; Social status in art; Sozialstatus; Kunst; Mäzenatentum; Italien